The Presence of Antithyroid Antibodies in Euthyroid Patients with Unexplained Infertility - Simrun; Majid , Erum; Zehra, Tamkeen; Nasir, Fatima; Kumar, Ameet (Indus Journal of Bioscience Research, 2025)
Objective: To determine the presence of antithyroid antibodies in euthyroid patients presenting with unexplained infertility. Study Design: Cross-sectional study. Place and Duration of Study: This study was conducted at the Department of Obstetrics and Gynecology, Jinnah Postgraduate Medical Centre (JPMC), Karachi, over a period of six months following approval of synopsis. Methodology: A total of 156 infertile women aged 20 to 45 years with confirmed euthyroid status and no identifiable cause of infertility were included through random sampling. Patients with known causes of infertility or any signs of thyroid dysfunction were excluded. After obtaining informed consent, participants underwent thyroid function tests including TSH, FT3, and FT4, along with anti-thyroid peroxidase (TPO) antibody measurement using ELISA. Data were recorded using a structured proforma and analyzed using SPSS version 26. Results: Out of 156 euthyroid women with unexplained infertility, 29 (18.6%) tested positive for TPO antibodies while 127 (81.4%) were negative. TPO antibody positivity was significantly associated with infertility duration greater than two years (p=0.03) and history of early pregnancy loss (p=0.02). Mean age, TSH, FT4, and FT3 levels showed no statistically significant differences between the two groups. Conclusion: A considerable proportion of euthyroid women with unexplained infertility were found to have TPO antibody positivity, suggesting an underlying immunological mechanism. Routine screening for antithyroid antibodies should be considered in the diagnostic workup of unexplained infertility to enable early intervention and improve reproductive outcomes.